ZEITLICHE UND REGIONALE UNTERSCHIEDE IN DER VERBREITUNG DES NEUEN STILS DER UNGARISCHEN VOLKSMUSIK IN SIEBENBÜRGEN - István ALMÁSI (Studia Universitatis Babeş-Bolyai. Musica)
Recent investigations demonstrated that Béla Bartók’s opinion was correct when he stated that the new style of the Hungarian folk music emerged in the 19th century. In addition it has been proved that in the history of the new style there can be distinguished an early and a developed stage, both with characteristic features and especially the developed new melodies spread rapidly in every direction in the last two decades of the 19th century. However at least in two regions of Central Transylvania the melodies of the new style remained unknown until the years of World War I. This circumstance became evident on the basis of two folk song collections compiled at the beginning of the 20th century.